Strategy for Development of the Central Wologai Traditional Village Tourism Attraction Area, Detusoko District, Ende Regency - Imelda Aurensia Rosalia; Apriana H. J. Fanggidae; Novi Theresia Kiak (Formosa Journal of Sustainable Research, 2023)
This study aims to find out the strategy for developing tourism in the Wologai Tengah Traditional Village so that it can become a tourist attraction that can attract many visitors and to find out what components are needed in the development of Wologai Traditional Village tourism using SWOT analysis. This research use desciptive qualitative approach. The collection of data used is interview, observation and documentation. The results of the research determine the policies that should be prioritized by the local government in an effort to develop Wologai Traditional Village Tourism objects. So the results of this study indicate that the most effective strategy can have a positive impact on increasing visitors and tourist attraction income. Having event activities in the Wologai Traditional Village is one of the strategies to attract visitors to come. Promotion is also needed with the aim of introducing the Wologai Traditional Village Tourism Object